Examining Community Engagement in Heritage Conservation through Geopark Experiences from the Asia Pacific Region - Sharina Abdul Halim; Nor Azizah Ishak (Kajian Malaysia, 2017)
Conserving heritage is significant because it reflects and builds local community identities, assists in promoting sustainability and provides sense of place. Geopark concept promotes three main components, namely conservation of heritage resources, provision of tourism infrastructure and local socioeconomic development. Strengthening local community engagement through active participation is pertinent to ensure success of geopark implementation. Engaging local community in heritage conservation collaboratively with other stakeholders is crucial as it has the potential to transform values, practices and overall behaviour towards sustainability. Nevertheless, how local community is engaged has been contested because often the term community engagement used in development process does not fully reflect the extent to which local community is actually able to participate. The main objective of this article is to examine local community engagement in heritage conservation, using geopark experiences from the Asia Pacific region. Analysis of findings will be discussed qualitatively in twofold: firstly, based on results from reviews of secondary data resources and official geopark websites, secondly through survey obtained from 30 participants, from aspiring and UNESCO Global Geoparks member countries, who attended the Asia Pacific Geopark Network (APGN) Regional Course on Geoparks in 2015 and 2017. Heritage conservation, in geopark-based activities, is expressed in various ways, amongst which as a cultural process, such as social interaction of festivals and exhibitions, as well as in natural resource management. In general, main findings indicated there are room for opportunities in geopark-based activities to encourage social learning from local community and stakeholders on heritage conservation. It is pertinent that local community are engaged in activities that would strengthen their sense of belonging as local custodians towards promoting sustainable resource utilisation in balancing conservation with development.